A low-temperature coating method with H3BO3 for enhanced electrochemical performance of Ni-rich LiNi0.82Co0.12Mn0.06O2 cathode. (1st August 2022) - Chen, Jinyu; Su, Baitao; Fan, Jiang; Chu, Binbin; Li, Guangxin; Huang, Tao; Yu, Aishui
Abstract: Layered LiNix Coy Mn1− x −y O2 (NCM) materials have shown great potential in the field of electric vehicles. However, the increasing nickel content in Ni-rich ternary materials causes a dramatic degradation in their capacity retention. Meanwhile, the poor structure stability, as well as the high amount of residue lithium, give rise to the concerns of safety issues. Here, we put forward a simple method to convert residue lithium to coating compounds by directly mixing the LiNi0.82 Co0.12 Mn0.06 O2 powders with boron acid and then getting the mixture heated at a low temperature. Transmission electron microscopy (TEM) and X-ray photoelectron spectrum (XPS) prove that the boron-contained compounds are successfully introduced to the surface of the matrix. The electrochemical performance of the boron-coated sample presents great improvement with a capacity loss of less than 2% and a distinctly suppressed electrochemical resistance increase after cycling at 1C for 100 times. This study demonstrates that the boron-contained coatings give effective protection to Ni-rich cathode materials and the low-temperature heating process seems to be an ideal treatment to endow the boron-coated materials with better electrochemical performance.